CFD Simulation and Statistical Analysis of Experimental Designs for Blood Flow in T-Junction Vessels - Dianita, Cindy; Nastasya, Catherine (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
The blood vessel area that has the greatest chance of atherosclerotic plaque deposition is the bifurcation zone (branching) in the carotid artery. The non-Newtonian fluid of blood has the characteristics of a shear-thinning fluid. Computational Fluid Dynamics (CFD) simulation is used in this study to analyse hemodynamic in carotid artery flow with variations of vessel geometry. The branching geometry of the arteries is represented by a T-junction model which is the ideal simplified blood vessel geometry model to exhibit the most common behaviour in arterial bifurcations. The geometry of the T branch is varied into 4 different combinations of diameter size. Thus, the 2k factorial experimental design method is also used to investigate the effect of the inflow and outflow domain sizes on the response variables in the form of velocity values, Wall Shear Stress (WSS), and Oscillatory Shear Index (OSI). The results of this simulation can greatly help medical scientists to more easily predict areas that have the potential to form atherosclerotic plaques in the circulatory system.Keywords - Atherosclerotic Plaque, Blood Vessel, Computational Fluid Dynamics Non-Newtonian Fluid, 2k Factorial Method.